The Effects of AHCC®, a Standardized Extract of Cultured Lentinura edodes Mycelia, on Natural Killer and T Cells in Health and Disease: Reviews on Human and Animal Studies - Min Sun Shin; Hong-Jai Park; Takahiro Maeda; Hiroshi Nishioka; Hajime Fujii; Insoo Kang (Journal of Immunology Research)
Mushrooms have been used for various health conditions for many years by traditional medicines practiced in different regions of the world although the exact effects of mushroom extracts on the immune system are not fully understood. AHCC® is a standardized extract of cultured shiitake or Lentinula edodes mycelia (ECLM) which contains a mixture of nutrients including oligosaccharides, amino acids, and minerals obtained through liquid culture. AHCC® is reported to modulate the numbers and functions of immune cells including natural killer (NK) and T cells which play important roles in host defense, suggesting the possible implication of its supplementation in defending the host against infections and malignancies via modulating the immune system. Here, we review in vivo and in vitro effects of AHCC® on NK and T cells of humans and animals in health and disease, providing a platform for the better understanding of immune-mediated mechanisms and clinical implications of AHCC®.